2018
DOI: 10.1108/k-07-2017-0246
|View full text |Cite
|
Sign up to set email alerts
|

A model for examining the factors impacting the near field communication technology adoption in the organizations

Abstract: Purpose Organizations are social entities comprising multiple people that are goal-directed and have coordinated activities that are also linked to the external environment. As information technology improves, the organizational performance is also improved and it results in positive changes and development in the organizations. Near field communication (NFC) is one of such technologies that can be implemented and utilized in an organization. The purpose of this paper is to investigate the important variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 105 publications
2
20
0
Order By: Relevance
“…It was interesting to find that cost saving shows a positive effect on the perceived ease of use and is supported by other studies [89,[92][93][94]. Moreover, cost saving also shows a positive effect on the perceived usefulness and is supported by previous studies [89][90][91]. The findings indicate that distributed ledger technology could lessen the transaction cost, although delivering clear information for entry to many groups, and counting groups that verify monitoring compliance.…”
Section: Major Findingssupporting
confidence: 72%
See 1 more Smart Citation
“…It was interesting to find that cost saving shows a positive effect on the perceived ease of use and is supported by other studies [89,[92][93][94]. Moreover, cost saving also shows a positive effect on the perceived usefulness and is supported by previous studies [89][90][91]. The findings indicate that distributed ledger technology could lessen the transaction cost, although delivering clear information for entry to many groups, and counting groups that verify monitoring compliance.…”
Section: Major Findingssupporting
confidence: 72%
“…The authors of [88] identified that the higher the effort taken by the user to participate in self-service, the lesser the amount the user usually expects to pay for that service. The previous findings confirm that cost saving has a positive effect on Perceived ease of use [89][90][91]. Moreover, cost saving has a positive effect on perceived usefulness [92][93][94].…”
Section: Cost Savingsupporting
confidence: 61%
“…It is a model where every‐day objects for realizing some objectives can recognize, sense, and process the abilities to communicate with others on the Internet (Karahoca et al., 2018; Whitmore et al, 2015). NFC is a short‐range wireless communication technology that allows the communication of data packets among gadgets within a small area (Mohandes, 2015; Museli & Navimipour, 2018). It is occasionally confused with Radio Frequency Identification (RFID) or Bluetooth.…”
Section: Introductionmentioning
confidence: 99%
“…A focal firm requires supply chain agility to produce products according to the variable needs of customers. The companies respond quickly to volatile demand and short product life-cycles through supply chain agility (Museli and Jafari Navimipour, 2018). Using supply chain agility is required to produce new products according to the needs of customers (Tarafdar and Qrunfleh, 2016).…”
Section: Introductionmentioning
confidence: 99%